DO-TPR*-tree: A density optimal method for TPR*-tree - Phuong, Nguyen Tien; Duc, Dang Van (Journal of Computer Science and Cybernetics, 2015)
This paper proposes a density optimal method, named as DO-TPR*-tree, which improves the performance of the original TPR*-tree significantly. In this proposed method, the search algorithm will enforce firing up MBR adjustment on a node, if the condition, based on density optimal for the area of its MBR, is satisfied at a query time. So, all queries occurred after that time will be prevented from being misled as to an empty space of this node. The definition of Node Density Optimal is also introduced to be used in the search algorithm. The algorithm of this method is proven to be correct in this paper. Several experiments and performed comparative evaluation are carried out. In the environment with less update rates (due to disconnected) or high query rates, the method can highly enhance query performance and runs the same as the TPR*-tree in other cases.